Evaluation of the Effectiveness of a Total Extraperitoneal Abdominal Wall Lift for an Obturator Hernia - Katsumoto, Mitsuru; Matsuo, Hideki; Nakano, Masahiko; Yoshida, Tadashi; Furukawa, Satoshi; Kojima, Satoshi; Kaku, Hideaki (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2018)
An obturator hernia is a relatively rare disease；however, in the event of onset, it is accompanied by ileus and often requires emergency surgery. Moreover, the surgical methods are also controversial. At our hospital, a total extraperitoneal (TEP) lifting procedure is usually the first choice for obturator hernia, including incarcerated cases, so the effectiveness thereof was examined. The subjects included 16 obturator hernia patients (1 male, 15 female, average age 83.3) who underwent surgery at our hospital from January 2006 to December 2017. Among the subjects, while 7 patients underwent emergency surgery immediately after visiting our hospital, in 8 patients the incarceration spontaneously abated and 1 patient was able to undergo elective surgery due to manipulative reduction using ultrasonic probes. Other than 2 patients requiring intestinal resection, 14 patients were repaired with the TEP lifting procedure using 3DMAXTM Light Mesh. The average surgical time was 68 minutes, with an average length of hospitalization following surgery of 16.4 days. As postoperative complications, 1 case of femoral abscess formation and 1 case of exacerbation of heart failure were observed；however, there was no recurrence of the obturator hernia within the observation period from 5 months to 11 years. The TEP lifting procedure is believed to be a very effective technique for the treatment of obturator hernia.